Broiler Chickens Weight Prediction Base On Feed Out Using Backpropagation - Putra, Andre Mariza (Jurnal Sains dan Informatika, 2016)
The purpose of this study was to determine the weight of broiler chickens based feed that has been used up, so it can be to predict. Taking into account the things that affect the total weight of broilers such as total number of chickens were harvested and total feed consumed. Analysis of heavy broilers using primary data and secondary data. In this study designed systems using Artificial Neural Networks Backpropagation method and Matlab software.